THE ESSENCE OF MODERNISM IN JAMES JOYCE’S A PORTRAIT OF THE ARTIST AS A YOUNG MAN - T. R., Deepak; K. M., Prasannakumar; Naveen. S.; H. P., Suma. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Literature is an eternal mechanism to document the experiences of people in diverse forms. It also acts as the storehouse of different features witnessed in the course of literary movements. Many writers have considered literature as a platform to historicise the changes or spirits of society. James Joyce is one of the exponents of literature who provides the required impetus to represent modernity in the literary expressions. His novel A Portrait of the Artist as a Young Man (1916) has exemplified modernism in a European society. He has touched upon the evolving, fascinating, challenging and established structures like commerce, religion, tradition, and social life. His works have exhibited the characteristics of modernism, including a strong desire to break free from the constraints. They deal with the search for solutions and a place for man in the universe; and experiments with form and style. Even he is observed as a typical writer of modernist elements which have seriously influenced the evolution of modernist literary movement. Many techniques are introduced in the field of English literature with the intension of foreseeing transformations in the human ecosphere. The literary styles, themes, structures, and techniques have been able to elevate and provide the world of literature a new dimension. In literature, the ‘Stream of Consciousness’ is typified as a sober and sublime technique; which is possessed with the characteristic feature of modernity. Even the linguistic and language principles have been treated as the modern techniques to absorb the transformative elements of human civilization. All these modern techniques are universal in nature with genuine and subtle variations. These modern techniques assist the readers to comprehend and synthesize the virtues of an artist embedded in his portrait by means of the stream of consciousness and interior monologue. Hence, the research paper unfolds the essence of modernism represented in James Joyce’s A Portrait of the Artist as a Young Man within the contemporary charter.